METFORMIN DURING ADULTHOOD CANNOT ATTENUATE THE HARMFUL EFFECTS OF NEONATAL OVERNUTRITION (Arquivos do Mudi, 2023)
Under- or overnutrition, during critical periods of development, lead to the development ofobesity and cardiometabolic dysfunction later in life in rats that have been programmed forthe development of metabolic dysfunction in a litter reduction model. On day 1, all litters arestandardized to 9 pups per dam and on day 3 after birth, litters were adjusted to 3 pups perdam in the small litter group (SL) and the NL group remained with 9 animals. At 70 days ofage, the animals were separated into 2 new groups: Saline (SAL) and Metformin (MET). For12 days, the NL and SL animals were treated daily with saline, giving rise to the NL-SAL andSL-SAL groups, or were treated with Met 100mg/kg/day, giving rise to the NL-MET and SL-MET groups. The treatment ended at 82 days of age and the animals were taken up to 142days of life. Body weight remained significantly higher in SL compared to NL animals up to142 days (p<0.0001), with no significant difference in relation to treatment. And the samewas observed in relation to glucose intolerance and insulin resistance (p<0.0001). We canconclude that short-term treatment with metformin did not attenuate the metabolicdysfunction induced by neonatal overnutrition.